2022
DOI: 10.1002/pssa.202100505
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Microwave Absorbing Properties of Nd3+‐Doped Ni–Zn Ferrite/PANI Nanocomposite for Ku Band

Abstract: Nanosized ferrite is one of the new type of magnetic materials which exhibits better magnetic properties than the bulk form and therefore can be used in many fields such as chemical industries, electronic equipment, aerospace, defense, etc. Moreover, these ferrites are used in high-capacity storage devices, electromagnetic shielding, cores, magnetic separation, gas sensors, biosensors, humidity sensors, sodium ion batteries, solar cells, ferrofluilds, switching, high-frequency electromagnetic absorbing materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that porous structures can reduce the electromagnetic wave reflection through impedance matching. By enhancing multiple reflections and scattering of microwaves in the interior of materials, the porous structure can also extend the electromagnetic wave transmission channel. ,,, Porous materials, with a low density, a large specific surface area, and an adjustable porous structure, are ideal for electromagnetic wave absorption and are anticipated to broaden the EAB. ,, Although porous materials like aerogel and sponge foam mentioned in some current research have good absorption properties, they are poor in strength, heat resistance, and other properties required for practical applications. , …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that porous structures can reduce the electromagnetic wave reflection through impedance matching. By enhancing multiple reflections and scattering of microwaves in the interior of materials, the porous structure can also extend the electromagnetic wave transmission channel. ,,, Porous materials, with a low density, a large specific surface area, and an adjustable porous structure, are ideal for electromagnetic wave absorption and are anticipated to broaden the EAB. ,, Although porous materials like aerogel and sponge foam mentioned in some current research have good absorption properties, they are poor in strength, heat resistance, and other properties required for practical applications. , …”
Section: Introductionmentioning
confidence: 99%